Low Incidence of Avian Predation on the Brown Marmorated Stink Bug, Halyomorpha halys (Hemiptera: Pentatomidae), in Southeastern Orchard Systems - Erin E. Grabarczyk; Ted E. Cottrell; Jason M. Schmidt; P. Glynn Tillman (Insects, 2023)
In many agroecosystems, brown marmorated stink bugs (Halyomorpha halys) (Hemiptera: Pentatomidae) are polyphagous pests that cause significant economic losses to numerous crops every year. Insectivorous birds may provide a means of sustainable predation of invasive pests, such as H. halys. In forest margins surrounding peach, pecan, and interplanted peach–pecan orchards, we monitored H. halys populations with pheromone-baited traps, mist-netted birds, and collected avian fecal samples for molecular gut content analysis. We screened 257 fecal samples from 19 bird species for the presence of H. halys DNA to determine whether birds provide the biological control of this pest. Overall, we found evidence that four birds from three species consumed H. halys, including Northern cardinal (Cardinalis cardinalisis), Tufted titmouse (Baeolophus bicolor), and Carolina wren (Thryothorus ludovicianus). Halyomorpha halys captured in traps increased over time but did not vary by orchard type. Although incidence of predation was low, this may be an underestimate as a result of our current avian fecal sampling methodology. Because birds are members of the broader food web, future studies are needed to understand avian ecosystem services, especially in terms of pest control, including H. halys and other pest species.